Exploring Pathways for Rural Revitalization through Multi-Party Synergistic Participation: A Case Study of YY Company’s Involvement in W District, S City (Journal of Global Humanities and Social Sciences, 2025)
Against the backdrop of the in-depth advancement of the rural revitalization strategy, a single actor can no longer meet the diversified development needs of rural areas, making it urgent to establish a pluralistic co-governance pattern of “government guidance, corporate collaboration, and villager participation.” Using the case of YY Company’s participation in the “Rural Revitalization Demonstration Belt” project in Xihe Town, W District, S City, this paper, grounded in collaborative governance theory, constructs a “driving force–structure–process” analytical framework to systematically explore how enterprises, through cultural heritage excavation, resource integration, market linkage, and organizational mobilization, work in synergy with governments, village collectives, and villagers to jointly promote the revitalization of rural industry, ecology, culture, and governance. The findings reveal that enterprises, acting as hub-type actors, can not only stimulate the endogenous cultural dynamism of rural communities, facilitate factor reorganization and market transformation, but also enhance villagers’ organizational capacity and participation in public affairs through institutionalized collaborative mechanisms. Based on these findings, the paper proposes pathways such as establishing a tripartite collaborative mechanism among “government–enterprise–village collective,” institutionalizing collaborative governance processes, and strengthening bidirectional empowerment, offering a replicable and scalable model for enterprise participation in rural revitalization.